HtComp: bringing reconfigurable hardware to future high-performance applications. (2018) - Cilardo, Alessandro
Current trends in computer architecture are increasingly moving towards heterogeneous platforms, now including FPGAs as first-class components enabling unprecedented levels of performance and power-efficiency. Programming such next-generation machines is however extremely difficult as it requires architecture-specific code and low-level hardware design. This paper describes the main outcomes of the HtComp project, a two-year research programme aimed at exploring methodologies and tools allowing the automated generation of FPGA-based accelerators from high-level applications written in traditional software languages. In particular, the paper describes the main contributions brought by the project, covering the generation of hardware systems from high-level parallel code, the performance-oriented optimisation of memory architectures tailored on the application access patterns, as well as the automated definition of application-driven special-purpose on-chip interconnects. Overall, the above innovations contributed to creating a viable path allowing generic software developers to access tomorrow's hardware-accelerated high-performance platforms with minimum development overheads.